Preclinical Long-Term Stability and Forced Degradation Assessment of EPICERTIN, a Mucosal Healing Biotherapeutic for Inflammatory Bowel Disease - Wendy M. Kittle; Micaela A. Reeves; Ashley E. Fulkerson; Krystal T. Hamorsky; David A. Morris; Kathleen T. Kitterman; Michael L. Merchant; Nobuyuki Matoba (Pharmaceutics)
Background/Objectives: EPICERTIN, a biotherapeutic candidate for mucosal healing in inflammatory bowel disease (IBD) and other mucosal disorders, was subjected to an extensive long-term stability program to evaluate its molecular stability and physicochemical properties. Additionally, a forced degradation assessment was conducted to identify EPICERTIN’s degradation products under various conditions, including thermal stress, pH variations, agitation, and oxidation. Methods: The stability of EPICERTIN drug substance (DS), formulated in phosphate-buffered saline (PBS) at 1 mg/mL and stored at 5 °C and 25 °C/60% relative humidity (RH), was monitored over a 2-year period, referencing relevant regulatory guidelines. Evaluations of EPICERTIN DS over the 24-month period included assessment of purity by SDS-PAGE and size exclusion high performance liquid chromatography (SEC-HPLC), identity by electrospray ionization mass spectrometry (ESI-MS) intact mass analysis and Western blotting, and potency by GM1-binding KDEL-detection ELISA (GM1/KDEL ELISA). The forced degradation patterns were analyzed by assessing purity (using SEC-HPLC and SDS-PAGE), potency (via GM1/KDEL ELISA), and intact mass (via ESI-MS). Results: The results overall support that EPICERTIN DS remains stable for 2 years under the tested conditions. The forced degradation assessment effectively identified degradation products, particularly under conditions of high temperatures (above 40 °C for 24 h), low pH values (pH 1 and 4), and oxidation upon exposure to 2% H2O2. Conclusions: These findings highlight EPICERTIN’s robust long-term stability in PBS formulation, reinforcing its potential as a viable drug candidate for the treatment of IBD.